2020
DOI: 10.3390/toxics8010010
|View full text |Cite
|
Sign up to set email alerts
|

Enchytraeus crypticus Avoid Soil Spiked with Microplastic

Abstract: Microplastics (MPs) of varying sizes are widespread pollutants in our environment. The general opinion is that the smaller the size, the more dangerous the MPs are due to enhanced uptake possibilities. It would be of considerably ecological significance to understand the response of biota to microplastic contamination both physically and physiologically. Here, we report on an area choice experiment (avoidance test) using Enchytraeus crypticus, in which we mixed different amounts of high-density polyethylene mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The factors accounting for these varying effects are not yet known, and there are a multitude of factors that could contribute to the toxicity of the MP such as the diversity of possible microbes present in biofilms that form on the caps, the ink used, water hardness, time since discarding and so on. Concerning MP in soil, it is clear that changes in soil structure and biodiversity, as well as aggregate formation, are expected [45,46]. For example, less than 2% of the polyester microfibers present in soil can destabilize soil aggregates [45,47].…”
Section: Potential Relationship Between Mp Toxicity and Environmental Factorsmentioning
confidence: 99%
“…The factors accounting for these varying effects are not yet known, and there are a multitude of factors that could contribute to the toxicity of the MP such as the diversity of possible microbes present in biofilms that form on the caps, the ink used, water hardness, time since discarding and so on. Concerning MP in soil, it is clear that changes in soil structure and biodiversity, as well as aggregate formation, are expected [45,46]. For example, less than 2% of the polyester microfibers present in soil can destabilize soil aggregates [45,47].…”
Section: Potential Relationship Between Mp Toxicity and Environmental Factorsmentioning
confidence: 99%
“…Terrestrial ecosystems might face MPs pollution earlier than the aquatic ecosystems, and it is currently unknown what impacts MPs might have on the exposed organisms in soil or other substrate systems. Changes in soil structure and terrestrial geochemistry (water holding capacity, hydraulic conductivity, soil aggregation and microbial activity) already have been shown [14,15] which could affect the soil community [16].…”
Section: Introductionmentioning
confidence: 99%
“…Applying a less tiresome approach could optimize the counting of all juveniles in the selected area and demonstrate the same statistical difference. Domene et al (2011) reported a growing interest in developing an alternative ecotoxicological assessment that overcomes the reproduction as the final result for potworms, as currently some extra analysis can be performed such as gene expression (Gomes et al 2018), feeding activity (Bart et al 2018), avoidance behavior (Pflugmacher et al 2020), and Kinect uptaking (Mendonça et al 2020). Although these advanced techniques are valuable in bioassessment, some of them need the basal values of effective concentrations generated by the reproduction test to deepen their analysis.…”
Section: Resultsmentioning
confidence: 99%